2014
DOI: 10.3354/meps10660
|View full text |Cite
|
Sign up to set email alerts
|

Southern elephant seal foraging success in relation to temperature and light conditions: insight into prey distribution

Abstract: The distribution of southern elephant seal Mirounga leonina prey encounter events (PEEs) was investigated from the foraging behaviour of 29 post-breeding females simultaneously equipped with a satellite tag, a time−depth recorder and a head-mounted accelerometer. Seal diving depth and PEE were related to water temperature at 200 m (T 200 ), and light level at the surface (L 0 ) and at depth. Approximately half (49%) of all dives were located in waters encompassed between the southern Antarctic Circumpolar Curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
131
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(143 citation statements)
references
References 75 publications
8
131
0
Order By: Relevance
“…We suggest that during the summer seals adopt a hierarchical foraging strategy by responding to large-scale biological cues during late spring/summer phytoplankton bloom periods in order to locate profitable prey fields at the smaller scale. These findings are consistent with Guinet et al (2014) which showed summer seals (females) feeding during the day are more successful (indicated by prey capture attempts derived from accelerometer data) in areas where higher concentration of particles (indicted by the influence of plankton density on light attenuation) are encountered, but did not however consider females feeding in winter.…”
Section: Seasonally-contrasted Foraging Strategies In Relation To Ressupporting
confidence: 80%
See 1 more Smart Citation
“…We suggest that during the summer seals adopt a hierarchical foraging strategy by responding to large-scale biological cues during late spring/summer phytoplankton bloom periods in order to locate profitable prey fields at the smaller scale. These findings are consistent with Guinet et al (2014) which showed summer seals (females) feeding during the day are more successful (indicated by prey capture attempts derived from accelerometer data) in areas where higher concentration of particles (indicted by the influence of plankton density on light attenuation) are encountered, but did not however consider females feeding in winter.…”
Section: Seasonally-contrasted Foraging Strategies In Relation To Ressupporting
confidence: 80%
“…Due to distinct biological change between the summer bloom period and the winter post-bloom period, we expect fundamental differences in SES foraging strategy in relation to seasonal plankton densities. The diet of female SES is thought to consist largely of mesopelagic fish, primarily myctophid, during the two foraging periods (Cherel et al, 2008;Guinet et al, 2014). Therefore, seasonal changes in seal behavior may be indicative of a change in the prey field distribution relative to lower trophic (i.e., plankton) distribution.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, satellite-relayed data loggers (SRDLs) have been widely used for transmitting, in near real time, data on the behaviour of marine predators, most typically dive depth and duration, but also in some cases swimming speed or ocean data such as temperature and salinity [6,8]. The miniaturisation, extended battery life and memory capacity of these devices allow the collection and storage of data at very high resolutions (1 s or less) and for long periods of time (several months) [5,8,9]. However, the limited time and bandwidth available for data transmission at the surface imposed by both the animal's diving habits and CLS Argos restrict the amount of data that can be sent [6,10].…”
Section: Open Accessmentioning
confidence: 99%
“…The procedureis described in detail in Guinet et al (2014). Regardless of the axis, the recorded acceleration is composed of 2 types of acceleration: static and dynamic.…”
Section: Acceleration Datamentioning
confidence: 99%
“…Indeed, these loggers are focused on measuring prey capture attempts (PCAs), which is currently considered as the best proxy for foraging success (see Guinet et al 2014 where prey encounter events [PEE] correspond to PCA). However, the aforementioned devices may also have some restrictions.…”
Section: Introductionmentioning
confidence: 99%